Slow waves in magnetic metamaterials: history, fundamentals and applications - Shamonina, E. (physica status solidi (b), 2008)
Magnetic metamaterials consist of small metallic resonators of the split ring type. Microscopic properties of these structures are governed by near field coupling between individual elements. This strongly anisotropic coupling leads to propagation of slow magnetoinductive waves with the wavelength much shorter than that of the electromagnetic radiation. This opens up novel possibilities of designing miniaturised subwavelength waveguide components and near-field lenses in a wide range of frequencies, from radio frequencies, with a potential for medical applications in MRI, to the IR and visible range, aiming at fast signal processing. This paper provides an overview of contributions that led to the birth of the subject of magnetic metamaterials. The properties of slow waves on magnetic metamaterials including their dispersion characteristics, excitation and applications are discussed. The emphasis is laid on phenomena such as backward and forward slow waves, polaritonic hybridization of the interaction of a metamaterial with an incident electromagnetic wave yielding negative values of magnetic permeability, the possibility of positive and negative refraction of slow waves as well as mechanisms for near field subwavelength imaging.
EAM Import::2019-03-13